PEMBELAJARAN DARING MATERI PLSV SISWA KELAS VII DI MTs IBNU SINA SOREANG - Soimah Amaliatun Silmi; Ika Wahyu Anita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is a type of qualitative research that aims to describe online learning of one variable linear equation (PLSV) material for seventh grade students at MTs Ibnu Sina. The research subjects were 7 people, the selection of students was random. Data were obtained through student response questionnaires, interview guidelines and test questions.Â  Then the data obtained is analyzed and then presented in the form of a percentage according to the indicator. The results showed that students prefer face-to-face learning for mathematics. From the results of the study it was found that 85.7% of students prefer offline learning, one of the reasons is seen from the interaction factor, in online learning the interaction between students and teachers is limited. The student test results showed that there were 4 types of student errors in answering the questions, 1) understanding the questions, 2) compiling mathematical models, 3) completing mathematical models, and 4) interpreting the questions. The highest percentage is making a mathematical model as much as 57.1% of the 7 students who took the test.